HUBUNGAN ANTARA SELF-CONCEPT TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA MTSN 4 BANDUNG BARAT - Romlah, Siti; Novtiar, Chandra (Universitas Nusantara PGRI Kediri, 2018)
The purpose in this research is examine and describe the relationship between self-concept with students' mathematical creative thinking ability. The method used is descriptive with correlation technique. The population this research is all students of class VII MTSN 4 West Bandung academic year 2017/2018. The samples used were chosen by purposive sampling as many as 35 students. The data collected are test results of mathematical creative ability and questionnaires about self-concept. The instrument used consists of 5 questions of creative thinking ability in the form of a description and 24 statements about student self-concept. Statistical data processing was done by SPSS 21 software that uses product moment correlation test then the result is analyzed descriptively. Based on the research result, it can be concluded that there is a relationship between self-concept to the ability of mathematical creative thinking with correlation of 0.792 at the level of significance 0.000 and the coefficient of determination of 62,73% with good relationship classification. This means that variations in creative thinking can be explained by variations in self-concept, the higher the self-concept of the students ,the higher the ability to think mathematically.